2008
DOI: 10.2174/157340308783565410
|View full text |Cite
|
Sign up to set email alerts
|

Is Peri-Operative Isolated Systolic Hypertension (ISH) a Cardiac Risk Factor?

Abstract: We are presenting a review of Isolated Systolic Hypertension (ISH) as a cardiovascular risk factor with emphasis on the perioperative period.Isolated systolic hypertension is associated with aging and is the most frequent subtype (65%) among patients with uncontrolled hypertension. ISH is strongly associated with increased risks of cardiac and cerebrovascular events exceeding those in comparably aged individuals with diastolic hypertension. Patients with ISH show an increase in left ventricular (LV) mass and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 132 publications
0
5
0
Order By: Relevance
“…ISH is also known to be associated with an increased incidence of cardiovascular complications. Observational, epidemiologic and clinical trial data have demonstrated that elevated SBP significantly increased the risk of stroke, coronary heart disease, and end-stage renal disease, especially in individuals ≥ 65 years of age [5, 6]. IDH is associated with a low risk of cardiovascular disease (CVD) mortality, whilst ISH carries a similarly high risk to systolic-diastolic hypertension (SDH).…”
Section: Introductionmentioning
confidence: 99%
“…ISH is also known to be associated with an increased incidence of cardiovascular complications. Observational, epidemiologic and clinical trial data have demonstrated that elevated SBP significantly increased the risk of stroke, coronary heart disease, and end-stage renal disease, especially in individuals ≥ 65 years of age [5, 6]. IDH is associated with a low risk of cardiovascular disease (CVD) mortality, whilst ISH carries a similarly high risk to systolic-diastolic hypertension (SDH).…”
Section: Introductionmentioning
confidence: 99%
“…Among surgical departments, vascular surgery was identified as a risk factor for severe IOH. Patients who receive vascular surgery are generally elder and have higher pulse pressure and isolated systolic hypertension due to reduced arterial compliance resulting from increased arterial wall stiffness [ 14 , 15 ]. The increase in pulse pressure due to increased arterial wall stiffness is an independent factor defining sympathetic baroreflex sensitivity in the elderly [ 16 ], and can lead to blood pressure fluctuations due to impaired baroreflex sensitivity [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although Crowther et al [10] reported there was no association between preoperative hypertension and perioperative hemodynamic changes known to be associated with major morbidity and mortality. The sample sizes in most of the research mentioned above were small, leading to uncertainty in the relationship between systolic hypertension and surgical risk [4][5][6][7][8]20].…”
Section: Discussionmentioning
confidence: 99%
“…Some patients' blood pressure in the operating theater is so high that operations have to be postponed or even canceled, while their baseline blood pressure remains much lower or relatively normal [1,2]. There is no consensus on what level of SBP change from baseline to first SBP (delta SBP) poses a risk to patients during surgery [3][4][5][6][7][8][9][10][11].…”
mentioning
confidence: 99%